Phylogeography and comparative ecophysiology of Chrysanthemoides Turn. Ex Medik. (Tribe Calenduleae) - Howis, Seranne (Rhodes University, Faculty of Science, Botany Department, 2005)
Chrysanthem Oides is a common Southern African shrub that grows in a variety of habitats. From coastal shrubland and fynbos to mountainous areas as far north as Kenya. The genus has two species and 8 subspecies. The diagnoses and delimitation of which have been based almost exclusively on morphological characteristics. This project aims to investigate, with the use of phylogenetic species concepts. The validity of these subspecies. Unlike biological species concepts that rely on reproductive isolation as a defining character of a species. Phylogenetic species concepts (PSC) are concerned with delimiting evolutionary significant units (ESUs). ESUs are evolutionarily isolated lineages, and under the PSC a species is an aggregation of organisms consistently diagnosable by a fixed character or combination of characters. This project therefore searched for genetic and physiological characters by which to delimit ESUs within the Cill), samhemoides genus. DNA sequencing was used to investigate the genetic characters, while gas exchange studies were used to investigate the ecophysiological characters. DNA sequence analysis indicated that the ESUs can be diagnosed by genetic means and that one species may be of hybrid origin. Field studies of three disparate genetically identifiable ESUs from three disparate climates found that there are noticeable differences in ecophysiological responses of these ESUs in the field. Plants from each ESU were transferred to a greenhouse and grown under identical conditions for several months and compared to determine if these traits are inherent, or elastic in relation to environmental conditions. Under simulated high rainfall conditions. There does not appear to be a significant difference in the photosynthetic traits.
Keywords: Chrysanthemoides; Phylogeny; Ecophysiology; DNA; Plant genetics